Synthetic sustainability index (SSI) based on life cycle assessment approach of low impact development in the Mediterranean area. Issue 1 (1st January 2017) - Maiolo, M.; Carini, M.; Capano, G.; Piro, P.
Abstract: Climate change and the processes of urbanization alter the hydrologic and hydraulic regime of runoffs formation in urban areas. Low impact infrastructure development (LID) contributes to achieving conditions of invariance hydrological and hydraulics. The purpose of this work is to identify an index of synthetic sustainability (SSI) based on life cycle assessment (LCA). Such LCA evaluates design alternatives through the comparison of the different values of the SSI. The proposed methodology allows the evaluation of the SSI attributing to the individual layers of the LIDs different weights and taking into account both of the influence that each of them perform on invariance hydrologic and hydraulic both of the LCA normalized output. In this paper is showed a methodological implementation obtained by the analysis of a green roof and a permeable pavement. This green roof has been realized, on real scale, in the Urban Hydrology Experimental Park in University of Calabria (Italy).